1969
DOI: 10.1161/01.res.24.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Range of the Sympathetic Control of the Dog Femoral Artery

Abstract: Femoral arterial diameter and pressure were measured in anesthetized dogs. Immediately after section of the ipsilateral lumbar sympathetic chain the artery dilated, reaching a maximum of 122.0% (±0.56 SEM) of resting diameter within 30 to 40 seconds. Later the diameter diminished, stabilizing at 104.3% (±1.8 SEM) of resting diameter within 15 minutes. Stimulation of the peripheral stump of the sympathetic chain induced frequency-dependent constriction, the frequency-response curve being hyperbolic. The average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…In the current investigation, the lower arterial compliance was seen in the presence of an augmentation in sympathovagal balance. This augmentation has been shown to further reduce distensibility of small, medium, and large arteries, resulting in a tonic restraint of elastic and resistance type vessels (3,6,11,24,43). Independently and in combination, the loss of arterial compliance and alterations in autonomic function are associated with increased HT risk.…”
Section: Discussionmentioning
confidence: 99%
“…In the current investigation, the lower arterial compliance was seen in the presence of an augmentation in sympathovagal balance. This augmentation has been shown to further reduce distensibility of small, medium, and large arteries, resulting in a tonic restraint of elastic and resistance type vessels (3,6,11,24,43). Independently and in combination, the loss of arterial compliance and alterations in autonomic function are associated with increased HT risk.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum levels of diameter reduction induced in our study were comparable to those obtained by profound sympathetic stimulation in situ. 24 It is conceivable that circulating EDRF released at the luminal side of intact endothelium, proximal to the denuded area, can exert a dilator response in the denuded segment. However, there is evidence that a plasma factor (or factors) may inactivate the EDRF.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49] The improvement in BRS in this investigation could be in part due to a lesser sympathetic modulation and a well-known mediator of vascular stiffness. 20,50,51 Arterial compliance Loss of AC during sympathetic stimuli leads to exaggerated increases in an a 2 -adrenergic-mediated vasoconstriction and/or decreases in b 2 -adrenergicmediated vasodilation, both of which contribute to increases in arterial stiffness. Augmented and/or exaggerated sympathetic activity has been shown to further reduce distensibility of small, medium and large arteries, [49][50][51][52][53] and is a common denominator for risk factors related to hypertension.…”
Section: Baroreflex Sensitivitymentioning
confidence: 99%
“…20,50,51 Arterial compliance Loss of AC during sympathetic stimuli leads to exaggerated increases in an a 2 -adrenergic-mediated vasoconstriction and/or decreases in b 2 -adrenergicmediated vasodilation, both of which contribute to increases in arterial stiffness. Augmented and/or exaggerated sympathetic activity has been shown to further reduce distensibility of small, medium and large arteries, [49][50][51][52][53] and is a common denominator for risk factors related to hypertension. [54][55][56] Our prior study, and that of others, has shown that a strong relationship exists between .…”
Section: Baroreflex Sensitivitymentioning
confidence: 99%